Knowledge management & generational change: the impact on local small & medium enterprise - Ventura, Marzia; Cristofaro, Concetta Lucia; Melina, AnnaMaria; Reina, Rocco (Piccola Impresa / Small Business, 2014)
The paper wants to analyse the role and the impact of knowledge management in the development of local SME’s specifically linked to the stage of business succession and generational change. In SME’S the generational transition is critic and often become a real and complex situation to overcome. The aim of the work is to understand if knowledge management can be a lever with which it is possible to support the generational transition and what are the empirical mode used in some different organizations investigated, all of them engaged in this critical stage.The work in progress research is focused on the different actors and methods involved in the generational change. In this way different figures are investigated like entrepreneur and his/her next generation and management engaged, but otherwise the role of practical methods, guidelines, values and culture like specific forms of knowledge used in order to manage the business process.